Analysis Of The Impact Of Traditional Market Revitalization On Increasing Traders' Income (Case Study Of Pekkae Modern Market, Barru Regency) - Erwin Saputra; Siti Aisyah; Firman Syah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the impact of traditional market revitalization on increasing traders' income, focusing on the case of Pekkae Modern Market in Barru Regency. The market revitalization was initiated by the government to enhance the competitiveness of traditional markets in response to the growing dominance of modern markets. This study using a qualitative approach with a case study method. Data were collected through in-depth interviews with traders and market managers, as well as direct observations of the physical changes and market management post-revitalization. The findings indicate that the market revitalization has positively affected traders' income due to the increased consumer visits and improved market facilities, which have become more comfortable and orderly. Additionally, changes in stall arrangement, parking area expansion, and improvements in market cleanliness and security have also contributed to enhancing the market's appeal to consumers. Thus, traditional market revitalization can be considered an effective strategy in supporting the sustainability and development of traditional markets in the modern era.